The Photosensitizer from the Basic Dye Extract of the Skin Fruit of Eggplant (Solanum melongena L.) - Risnah, Indah Ayu; Aisyah, Aisyah; Iswadi, Iswadi; Saokani, Jawiana (Al-Kimia, 2018)
The latest generation of solar cell that utilizes dye from plants as a photosensitizer is Dye-Sensitized Solar Cell (DSSC). The dye from Solanum melongena L. is one of the potential photosensitizers due to its chemical and physical characteristics. This study aims to determine these characteristics as well as its efficiency value in DSSC. The dye was obtained by ultrasonic extraction in 1% HCl methanol solution. The crude extract of dye was treated in acid and basic condition and then separated by vacuum gravitation chromatography in a way that the polarity was increased. The results were a variety of dyes according to their polarity. The dye then applied in DSSC as the photosensitizers. The highest conversion value was 0.0211%, performed by the dye in pH 8 solution. The characteristic of this extract was identified by UV-Vis, FTIR, and GC-MS. All the spectral data indicated that the main component which responsible for this efficiency was pelargonidin.